Antibacterial Activity Of Musa Paradisiaca Var. Sapientum Peel Extrak Cream And Ointments Dosage Form On Staphylococcus Aureus - solikah ana estikomah (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2021)
The aim of the present study was to determine the difference of antibacterial effectivity between ointment  and cream Musa paradisiaca var. Sapientum (MPvS) peel extract against bacteria Staphylococcus aureus. Objective: To prove the antibacterial effect of banana peel extract with 5%,10%,15% concentration cream and oitments on Staphylococcus aureus. Methods: This study was applying the true experimental design with analyzed statistically with the ANOVA test and continued with the Duncan test to determine the level of treatment that provided the difference and the T-test to determine the most effective differences between groups. The results of the antibacterial activity of cream with a concentration of 10% with an inhibition zone diameter of 12.80 mm and Ointment at a concentration of 15% with an inhibition zone value of 11.07 mm were able to inhibit antibacterial activity. Conclusion, banana peel MPvS extract Cream Formula is the most effective in inhibiting the growth of Staphylococcus aureus bacteria.